Evaluating the performance of the Faculty of Economics in Tishreen University using the Data Enclosure Analysis (DEA) method. - زعبوب سامر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed at the following: evaluating the performance of Syrian universities through a case study of the University of Tishreet in its various faculties, using the linear programming method in the performance evaluation process, studying and analyzing the performance of the faculties of Tishreen University and comparing among them and determining its strengths and weaknesses with the possibility of providing solutions to overcome weaknesses, analyzing variables The performance represented by the educational and administrative dimensions in addition to the performance dimension represented by the number of graduates and during the academic year 2020-2021, and the results obtained are: - There is a statistically significant effect of the administrative dimension indicator on the performance of the faculties of Tishreen University. - There is a statistically significant effect of the educational dimension indicator on the performance of the faculties of Tishreen University. - We can evaluate the efficiency performance at Tishreen University using the linear programming method and generalize this to other higher education institutions. - There are differences between the levels of proficiency for each faculty separately at Tishreen University.